2014
DOI: 10.15171/ijhpm.2014.116
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between accreditation and patient satisfaction – the case of selected Lebanese hospitals

Abstract: This study brings to light the importance of embracing more adequate patient satisfaction measures in the Lebanese hospital accreditation standards. Furthermore, the findings reinforce the importance of weighing the patient perspective in the development and implementation of accreditation systems. As accreditation is not the only driver of patient satisfaction, hospitals are encouraged to adopt complementary means of promoting patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 22 publications
6
46
1
2
Order By: Relevance
“…Results did not show any significant differences based on age, economic status, educational level or nationality in accordance with Al-Qatari and Haran (1999) and Hayati et al (2010) 19,22 . Haj-Ali et al (2014) did not also find any significant relations between patient satisfaction, hospital's location and patient's socio-demographic characteristics 23 . Likewise, Al-Qahtani et al (2012) and Al Qatari and Haran (1999) stated no significant differences based on age between patients' perception on the quality of health care services 19,22 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Results did not show any significant differences based on age, economic status, educational level or nationality in accordance with Al-Qatari and Haran (1999) and Hayati et al (2010) 19,22 . Haj-Ali et al (2014) did not also find any significant relations between patient satisfaction, hospital's location and patient's socio-demographic characteristics 23 . Likewise, Al-Qahtani et al (2012) and Al Qatari and Haran (1999) stated no significant differences based on age between patients' perception on the quality of health care services 19,22 .…”
Section: Discussionmentioning
confidence: 92%
“…The reason might be the non consistency of accreditation standards with patients' needs which necessitates reexamining the standards to complement them in accordance with patients' desires. Another explanation is that accreditation programs are not confined to patients and related topics but are associated with all hospital's processes and outcomes covering a variety of clinical and non clinical aspects 10,22,23 . Patients at low accredited hospitals were more satisfied with the quality of services regarding to personnel, equipment and physical environment, information and communication, accessibility to clinical services, management and overall dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In the same review, the findings of 25% (4/16) of the reviewed studies apparently showed minimal difference in patient satisfaction in accredited hospitals (Almasabi et al 2014). Associations between accreditation and patient satisfaction were also not found in a study among selected Lebanese hospitals (Haj-Ali et al 2014). Sack et al (2011) surveyed 37,000 patients' who were discharged after four weeks from 73 hospitals in Germany.…”
Section: Introductionmentioning
confidence: 92%
“…Associations between accreditation and patient satisfaction were also not found in a study among selected Lebanese hospitals (Haj‐Ali et al . ). Sack et al .…”
Section: Introductionmentioning
confidence: 97%
“…Standar dapat dipromosikan dan direkomendasikan oleh sistem akreditasi nasional, sehingga memberi insentif bagi pasien di pelayanan kesehatan untuk mengumpulkan dan melaporkan kepuasan pasien. Data nasional tentang kepuasan pasien menyebutkan kebijakan pada tingkat sistem atau organisasi, peningkatan kualitas dan tingkat keterampilan SDM bertujuan untuk membantu kemajuan fasilitas pelayanan kesehatan (Haj-Ali, Karroum, Natafgi, & Kassak, 2014).…”
Section: Hasil Dan Pembahasanunclassified